Clinical and economic benefits of advanced microplegia delivery system in cardiac surgery: evidence from 250 hospitals. (23rd April 2018) - Gerdisch, Marc W; Robinson, Scott; David, Guy; Makepeace, Stephanie; Ryan, Michael P; Gunnarsson, Candace
Aim: Determine the impact of a second generation microplegia delivery system (MPS2) compared with traditional cardioplegia.Materials &  methods: Multivariable difference-in-differences analysis using fixed effects was performed for each outcome: adverse event (AE) composite, total visit cost, medication cost, length of stay (LOS) and  intensive care unit (ICU) days.Results: A 2.25% absolute risk reduction in AE composite was found with MPS2 compared with traditional cardioplegia, which equates to relative risk reduction of 5.25%. Significant reductions in LOS and ICU days (0.1 α level). Per case reduction of US$1231 total visit and US$192 medication costs were found in MPS2 hospitals.Conclusion: For hospitals with MPS2, significant reductions were seen in AEs, LOS and ICU days, which lead to reductions in total visit and medication costs.